تقويم مدى إشراك العاملين كأحد معايير إدارة الجودة الشاملة في تطوير الأداء الإداري في الاتحاد الرياضي العام في سورية - معوض, وائل; المصري, هبة (Latakia University Journal -Medical Sciences Series, 2017)
تهدف الدراسة إلى تقويم مدى إشراك العاملين كأحد معايير إدارة الجودة الشاملة في تطوير الأداء الإداري في الاتحاد الرياضي العام في سورية،واستخدمت الباحثة المنهج الوصفي المسحي لملاءمته لطبيعة الدراسة ، وتم إجراء الدراسة على عينة قوامها 100فرد من أعضاء المكتب التنفيذي والعاملين وأعضاء الاتحاد العاملين في مبنى الاتحاد الرياضي العام في دمشق وتم اختيارهم بالطريقة القصدية، وقد أسفرت نتائج الدراسة على أنه لا يوجد لجان خاصة بمتابعة الاحتياجات التدريبية للعاملين مما جعل عمليات التحسين المستمر غير مكتملة، و.أثر عدم الاهتمام بمناخ العمل الداخلي على أداء العاملين في الاتحاد الرياضي العام بالإضافة إلى غياب مفهوم إشراك العاملين كمعيار ممن معايير إدارة الجودة الشاملة للعينة ، وذلك لعدم إدراج إدارة الجودة الشاملة كنمط جديد من أنماط الإدارة في الاتحاد الرياضي العام كما أسفرت النتائج على أنه لايوجد فروق معنوية في استجابات العينة من حيث (الجنس، الصفة الإدارية ،الشهادة العلمية ، التفرغ ،عدد سنوات الخبرة) وبالتالي اتفقت العينة على عدم وجود اهتمام من قبل الاتحاد في تطبيق إشراك العاملين كمعيار من معايير إدارة الجودة الشاملة في التطوير الإداري في الاتحاد الرياضي سوريا، وعلى ذلك أوصت الباحثة إلى ضرورة تبني الاتحاد الرياضي العام في سوريا لثقافة الجودة الشاملة ونقلها لجميع فروع الاتحاد في المحافظات السورية ، وتكوين مكتب للجودة الشاملة من قبل إدارة الاتحاد الرياضي العام في سوريا يكون مسؤول عن تنفيذ برامج الجودة الشاملة في الاتحاد، والعمل على الارتقاء بالكفايات الشخصية والفنية للعاملين ليكونوا على مستوى إداري قادر على تنفيذ العمليات الإدارية بجودة عالية.The study aims to Assess the extant of n ivolvement of employees as one of total quality management standards in the development ofperforamnce in public sports Federation in SyriaKand the researcher has used the description and survey for being suitable with the study nature, The study covered a sample of 100 member of the Executive Committee, employees and members of SGSF in Damascus who have been chosen on purpose, The results revealed that it does not have a special follow-up for people training needs committees, making continuous improvement processes is incomplete, and lack of attention to the work environment effect on the performance of people in the SGSF as well as the absence of the concept of Engagement of people as a criterion whose overall sample quality management standards, due to lack of inclusion of TQM is a new style of management styles in the SGSF and The results revealed there is no significant difference in sample responses in terms of (sex, administrative capacity, Career, full-time, years of experience) and thus the sample agreed on the lack of an interest by the SGSF in the application of Engagement of people as a criterion of the overall quality of administrative development in the SGSF management standards, the researcher recommended that SGSF must adopt the culture of total quality in SGSF and transfer it to all SGSF branches, Composition of the Bureau of TQM by the SGSF management is responsible for the implementation of total quality programs in the SGSF, And the need for informed each people in the SGSF on total quality management program and consider it an essential part of the success of this program, And work to improve the competencies of personal and artistic people to be able to execute the administrative processes with high quality management level.